2011
DOI: 10.1016/s1995-7645(11)60108-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo anticancer activity of Indigofera cassioides Rottl. Ex. DC.

Abstract: The results strongly support that MEIC shows potent antitumor and cytotoxic effects against EAC, DLA and human cancer cell lines. The extract prevents lipid peroxidation and promotes the enzymatic antioxidant defense system in tumor bearing animals which might be due to activities like scavenging of free radicals by the phytochemicals in MEIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 17 publications
2
36
0
1
Order By: Relevance
“…Hence this study the cytotoxicity was evaluated in vitro. Studies have observed the presence of a large number of bioactive compounds in the methanolic extracts of this plant including tannins, alkaloids, steroids, saponins, terpenoids, and flavonoids which exhibit various biological activities [11][12][13][14][15][16][17] . These compounds are present in a number of food items and hold great potential as drug candidates due to their safety, low toxicity and wide acceptance amongst the public.…”
Section: Discussionmentioning
confidence: 99%
“…Hence this study the cytotoxicity was evaluated in vitro. Studies have observed the presence of a large number of bioactive compounds in the methanolic extracts of this plant including tannins, alkaloids, steroids, saponins, terpenoids, and flavonoids which exhibit various biological activities [11][12][13][14][15][16][17] . These compounds are present in a number of food items and hold great potential as drug candidates due to their safety, low toxicity and wide acceptance amongst the public.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed cell death or apoptosis performs an essential role for balancing cell proliferation and cell death and contributes to an effective cancer therapy [17][18][19][20][21][22][23][24] . Several anticancer activity studies have defined apoptosis as the pharmaco-dynamic endpoint for anti-cancer treatment [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Macroconidia were formed after [4][5][6][7] days from short multi-branched conidiophores which may form sporodochia. They are 3-septate, fusiform, cylindrical, often moderately curved, with an indistinctly pedicellate foot cell and a short blunt apical cell, (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) 毺m 暳 4-6 毺m). Microconidia are usually abundant, cylindrical to oval, oneto two-celled and formed from long lateral phialides, (8)(9)(10)(11)(12)(13)(14)(15)(16) 毺m 暳 2-4.5 毺m).…”
Section: Resultsmentioning
confidence: 99%
“…PCR was conducted for [30][31][32][33][34][35][36][37][38][39][40] cycles in a thermal controller (Programmable Thermal Controller; M) Research Inc., Watertown, MA). The primers used for amplification of p53 gene were shown in Table 1.…”
Section: Rt-pcr Analysismentioning
confidence: 99%